Another Radical Equation

Algebra Level 2

Find the real solution to

x 1 + x + 4 = 5. \sqrt{ x - 1 } + \sqrt{ x + 4 } = 5 .


The answer is 5.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

6 solutions

Chew-Seong Cheong
May 25, 2017

Given an equation similar to x 1 + x + 4 = 5 \sqrt{x-1}+\sqrt{x+4} = 5 , we can always let the smallest radical be u = x 1 \sqrt u = \sqrt {x-1} , then the equation becomes u + u + a = b \sqrt u+\sqrt{u+a} = b . In this example, a = b = 5 a=b=5 .

u + u + a = b u + a = b u Squaring both sides u + a = u 2 b u + b 2 2 b u = b 2 a u = ( b 2 a 2 b ) 2 For a = b = 5 u = ( 5 2 5 2 5 ) 2 x 1 = 4 x = 5 \begin{aligned} \sqrt u+\sqrt{u+a} & = b \\ \sqrt{u+a} & = b - \sqrt u & \small \color{#3D99F6} \text{Squaring both sides} \\ u + a & = u - 2b \sqrt u + b^2 \\ 2b \sqrt u & = b^2 - a \\ \implies u & = \left(\frac {b^2 - a}{2b}\right)^2 & \small \color{#3D99F6} \text{For }a=b=5 \\ u & = \left( \frac {5^2 - 5}{2\cdot 5}\right)^2 \\ x-1 & = 4 \\ \implies x & = \boxed{5} \end{aligned}

Rishabh Jain
May 24, 2017

In general: x 1 + x + 4 = n \sqrt{ x - 1 } + \sqrt{ x + 4 } = n x + 4 = n x 1 \sqrt{x+4}=n-\sqrt{x-1} Squaring we get: x + 4 = n 2 + ( x 1 ) 2 n x 1 x+4=n^2+(x-1)-2n\sqrt{x-1} x 1 = n 2 5 2 n , n 0 \implies \sqrt{x-1}=\dfrac{n^2-5}{2n}~~,n\ne 0 Squaring again gives: x = 1 + [ n 2 5 2 n ] 2 \boxed{x=1+\left[\dfrac{n^2-5}{2n}\right]^2} .

For n = 5 n=5 , we get x = 5 x=5 . A direct substitution in the original equation confirms the answer.

Calvin Lin Staff
May 24, 2017

[This is not yet a solution. If no one adds a non-trial and error solution in a week, I will flesh out the details.]

So, most people might eventually guess that x = 5 x = 5 gives us x 1 + x + 4 = 4 + 9 = 5 \sqrt{ x - 1 } + \sqrt{ x + 4 } = \sqrt{ 4 } + \sqrt{ 9 } = 5 .

However, this is somewhat haphazard, and doesn't allow us to solve the more general problem. In fact, how can we generalize the problem?

Mustafa Alelg
Oct 12, 2018

Lew Sterling Jr
May 21, 2019

x 1 + x + 4 = 5 x 1 + x + 4 x + 4 = 5 x + 4 x 1 = 5 x + 4 ( x 1 ) 2 = ( 5 x + 4 ) x 1 = x + 29 10 x + 4 x 1 x = x + 29 10 x + 4 x 1 = 10 x + 4 + 29 1 29 = 10 x + 4 + 29 29 30 = 10 x + 4 ( 30 ) 2 = ( 10 x + 4 ) 2 900 = 100 ( x + 4 ) 900 = 100 x + 400 900 400 = 100 x + 400 400 500 = 100 x 500 100 = 100 x 100 5 = x x=5 \begin{matrix} \sqrt{x-1}+\sqrt{x+4}=5\\ \sqrt{x-1}+\sqrt{x+4}-\sqrt{x+4}=5-\sqrt{x+4}\\ \sqrt{x-1}=5-\sqrt{x+4}\\ \left(\sqrt{x-1}\right)^2=\left(5-\sqrt{x+4}\right)\\ x-1=x+29-10\sqrt{x+4}\\ x-1-x=x+29-10\sqrt{x+4}-x\\ -1=-10\sqrt{x+4}+29\\ -1-29=-10\sqrt{x+4}+29-29\\ -30=-10\sqrt{x+4}\\ \left(-30\right)^2=\left(-10\sqrt{x+4}\right)^2\\ 900=100(x+4)\\ 900=100x+400\\ 900-400=100x+400-400\\ 500=100x\\ \frac{500}{100}=\frac{100x}{100}\\ 5=x\\ \textbf{x=5} \end{matrix}

Luke Dope
Jun 28, 2017

( √(x-1) + √(x+5) )²=5²
x-1+x+4+2√(x²+3x-4)=25
2x+2√(x²+3x-4)=22
x+√(x²+3x-4) =11
( √(x²+3x-4) )²=(11-x)²
x²+3x-4=121-22x+x²
25x=125
x=5






Nice. Sometimes squaring repeatedly to get rid of the roots work :)

Calvin Lin Staff - 3 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...